Scaling of Short‐Duration, Summer Rainfall Event Temporal Profiles With Warming Over Great Britain - Alexandra Seawell; Hayley J. Fowler; Stephen Blenkinsop; Caspar J. M. Hewett; Roberto Villalobos Herrera; Marie Hundhausen; Haider Ali (International Journal of Climatology, 2026)
The relationship between extreme rainfall and temperature, known as temperature scaling, is widely used to understand changes in rainfall characteristics under a warming climate. While most previous studies have focussed on fixed‐duration intensities or event totals, this study examines how different aspects of the rainfall temporal profile respond to temperature. Specifically, we focus on temperature scaling of total event depth, maximum sub‐hourly intensity and measures of profile concentration and loading. Using both sub‐hourly rain gauge data across Britain and 10‐min output from a convection‐permitting climate model (CPM) for present and future climates over southern England and Wales, we analyse short‐duration, summer rainstorms. Results show that total rainfall depth increases with temperature, with higher quantiles approaching Clausius‐Clapeyron (CC) scaling rates of 6–7%°C −1 . However, changes are unevenly distributed within the rainfall event temporal structure. Maximum sub‐hourly intensities scale more strongly than total event depth, with upper quantiles reaching 7–11%°C −1 , indicating pronounced intensification of short‐duration rainfall extremes at high temperatures. Accumulation of 50% of the rainfall event volume was found to occur over a shorter fraction of the storm duration and earlier in the storm duration, indicating rainfall events are more concentrated and more front‐loaded at higher temperatures, with both scaling at rates of 1–2%°C −1 . These results suggest that future summer rainstorms will not only deliver greater overall rainfall in a warming climate, but also produce more intense and earlier bursts of precipitation, heightening flash flood risk. Disregarding these temporal shifts may lead to underestimation of flood hazards and misrepresentation of climate change impacts in hydrological modelling and infrastructure design.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

In Vivo Clearance of Immune Complexes: Insights Into Human Drug/Anti-Drug Antibody Complex Clearance Dynamics - Eugenia Opolka-Hoffmann; Stephen Fowler; Thomas Bach; Gregor Jordan; Roland F. Staack (The AAPS Journal, 2026)
Immunogenicity of monoclonal antibodies (mAbs) and other biotherapeutics remains a significant clinical challenge. The resulting anti-drug antibodies (ADAs) can neutralize the drug, accelerate its clearance, diminish efficacy, and potentially trigger hypersensitivity reactions via the formation of immune complexes (ICs). Current pharmacokinetic (PK) and ADA assays typically measure the drug or ADAs but provide limited information on IC structure, concentration, and duration of exposure in humans. While rat studies suggest larger ICs are rapidly cleared, human dynamics are less understood. This study investigated IC formation and clearance in patients enrolled in a terminated Phase 1 clinical trial of TYRP1-TCB, a novel T-cell engager. Analysis of patient samples revealed that six patients, treated with 0.4 mg every three weeks, developed ADAs, resulting in IC formation. These complexes were evaluated using size exclusion chromatography (SEC) and enzyme-linked immunosorbent assay (ELISA). ICs of diverse sizes were detected, with larger ICs cleared faster than smaller ones. These findings highlighted the need for appropriate PK assays in clinical studies. Total drug PK assays alone may overestimate drug exposure during an immune response, as they do not distinguish between binding competent and ADA-bound drug. In contrast, active drug assays do not give any information on circulating drug that can no longer bind to the target. Neither approach gives information on circulating ICs, which may represent the majority of the drug administered following a strong ADA response. This study underscores the importance of understanding ADA and IC dynamics for ensuring the safe and effective use of biotherapeutics. Graphical Abstract

Atmospheric patterns associated with summer sub-daily rainfall extremes in western Europe - Anna C. Whitford; Stephen Blenkinsop; Hayley J. Fowler (Climate Dynamics, 2024)
Large-scale atmospheric circulations are a significant driver of rainfall extremes. However, little attention has so far been devoted to understanding how large-scale circulation patterns influence sub-daily rainfall extremes. Using a gauge-based sub-daily rainfall dataset, we investigate the relationship between large-scale circulations and 3-hour extremes (defined here as ≥ 40 mm rainfall in 3 h) for western Europe. A set of 30 weather patterns (WPs) developed by the UK Met Office and reanalysis data of geopotential height at 500 hPa (z500) are used to represent large-scale atmospheric conditions. Strong associations with 3-hour extremes are found for a small number of WPs: over 50% of 3-hour rainfall extremes across Western Europe occur with just 5 WPs. Composites of z500 reveal the WPs resulting in southerly or south-westerly flow along the leading edge of a trough, accompanied by a ridge to the east or northeast, are most favourable for sub-daily rainfall extremes, with a statistically significant difference between the atmospheric conditions on WP days with a 3-hour extreme rainfall event compared to WP non-event days. Given that large-scale circulations are predictable much further in advance than individual extreme rainfall events, these identified relationships could therefore have important implications for forecasting, aiding in the early identification of periods with increased risk of short-duration rainfall extremes.

Continued development of a tool to measure intramuscular fat of Australian lamb carcases in commercial situations - Stephanie M. Fowler; Stephen Morris; Suzanne I. Mortimer; David L. Hopkins (Meat Science, 2024)

Feasibility of tracking invasive Escherichia coli disease among older adults in a community setting: A prospective observational study - Joachim Doua; Miquel Ekkelenkamp; Theo Verheij; Oscar Go; Stephen Ruhmel; Kimberly Leathers; Bart Spiessens; Sanne van Rooij; Vance G. Fowler; Jeroen Geurtsen; Rowena Dolor; Michal Sarnecki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Invasive Escherichia coli disease (IED) encompasses a diverse range of sterile site infections. This study evaluated the feasibility of capturing IED among community-dwelling older adults to inform the implementation of a phase 3 efficacy trial of a novel vaccine against IED (NCT04899336). Methods EXPECT-1 (NCT04087681) was a prospective, multinational, observational study conducted in medically stable participants aged ≥ 60 years. At least 50% of participants were selected based on a history of urinary tract infection (UTI) in the previous 10 years. The main outcomes were the incidence of IED and the number of hospitalisations reported by the site vs participant. The length of follow-up was 12 months. In a US-based substudy, a smartphone-based geofencing was evaluated to track hospital entries. Results In total, 4470 participants were enrolled (median age, 70.0 years); 59.5% (2657/4469) of participants had a history of UTI in the previous 10 years. Four IED events were captured through deployment of different tracking methods: a self-report, a general practitioner (GP) report, and a follow-up call. The incidence rate of IED was 98.6 events per 100,000 person-years. The number of reported hospitalisations was 2529/4470 (56.6%) by the site and 2177/4470 (48.7%) by participants; 13.8% of hospitalisations would have been missed if utilising only site reports. Geofencing detected 72 hospital entries. Conclusion Deployment of multiple tracking methods can optimise detection of IED among community-dwelling older adults. Older adults with a history of UTI could be feasibly targeted for a phase 3 vaccine efficacy trial through a network of GPs.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

ENSO and IOD contributions to seasonal meteorological droughts over the Yangtze River basin - Hao Yin; Hayley J. Fowler; Stephen Blenkinsop; Zhiyong Wu; Hai He; Yuan Li (International Journal of Climatology, 2023)
The Yangtze River basin (YRB) has experienced frequent extreme drought events in recent years. Many studies have explored the impact of anomalous tropical sea surface temperatures on seasonal meteorological droughts over the YRB, yet two critical issues remain: (1) the regimes of the El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) causing YRB droughts; (2) the timing and spatial pattern of YRB droughts caused by ENSO and IOD. To address these knowledge gaps, we employed a comprehensive investigation. First, the Severity–Area–Density (SAD) method is applied to identify seasonal drought events over the YRB during 1971–2022. Second, we utilize composite analysis to specify the effects of ENSO and IOD. Our findings indicate that YRB droughts are significantly increased in the August of combined Eastern Pacific (EP) El Niño and positive IOD developing years, October of Central Pacific (CP) El Niño developing years, January of EP La Niña years, and April of CP El Niño decaying years. Third, we conduct numerical simulations and conclude that ENSO and IOD events contribute to the YRB droughts by modulating large‐scale circulation patterns, triggering the formation of cyclones and anticyclones over the Western North Pacific (WNP) and the Tibetan Plateau, and affecting the westerlies and other water vapour transport processes. These results on the physical mechanisms causing seasonal drought in the YRB can guide drought monitoring and prediction in the region.

The creation and climatology of a large independent rainfall event database for Great Britain - Roberto Villalobos Herrera; Stephen Blenkinsop; Selma B. Guerreiro; Hayley J. Fowler (International Journal of Climatology, 2023)
Extreme rainfall studies generally focus on hourly or daily rainfall accumulations. Additionally, studies focus on annual maxima (AM) or ‘peak intensities’. Although this approach is useful, the use of fixed‐duration accumulations simplifies inherently continuous rainfall processes which, at a rain gauge, are experienced as rainstorms of varying duration. A gap also exists in the study of sub‐hourly rainfall extremes which are an important source of flash floods. Here, we present the first large‐scale study of rainstorms in the United Kingdom. We leverage a recently created sub‐hourly resolution rain gauge dataset for Great Britain to identify over 70,000 rainstorms that generated AM rainfall intensities across a range of sub‐hourly to daily durations at 1279 rain gauges up to 2018. Our findings are consistent with previous studies of UK rainfall extremes and their climatology, where strong east–west differences are found in the magnitude of autumn and winter long‐duration (over 12‐h) rainstorms. We observe broad similarities in the behaviour of short (under 4‐h) rainstorms across GB, which are dominated by seasonal variations in convective activity rather than by geographical location. Our study reveals substantial overlaps between AM of different durations, with single rainstorms containing AM across a wide range of durations. We also demonstrate the substantial correlation between rainstorm duration and volume. These results challenge common independence assumptions used in the statistical modelling of rainfall extremes using extreme value theory. Our results represent an opportunity to refine rainfall design methods towards improved, robust representations of rainstorms.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Correction: Preclinical In Vivo Data Integrated in a Modeling Network Informs a Refined Clinical Strategy for a CD3 T‑Cell Bispecific in Combination with Anti‑PD‑L1 - Javier Sánchez; Valeria Nicolini; Linda Fahrni; Inja Waldhauer; Antje‑Christine Walz; Candice Jamois; Stephen Fowler; Silke Simon; Christian Klein; Pablo Umaña; Lena E. Friberg; Nicolas Frances (The AAPS Journal, 2023)

Preclinical InVivo Data Integrated in a Modeling Network Informs a Refined Clinical Strategy for a CD3 T-Cell Bispecific in Combination with Anti-PD-L1 - Javier Sánchez; Valeria Nicolini; Linda Fahrni; Inja Waldhauer; Antje-Christine Walz; Candice Jamois; Stephen Fowler; Silke Simon; Christian Klein; Pablo Umaña; Lena E. Friberg; Nicolas Frances (The AAPS Journal, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

New hourly extreme precipitation regions and regional annual probability estimates for the UK - Motasem M. Darwish; Mari R. Tye; Andreas F. Prein; Hayley J. Fowler; Stephen Blenkinsop; Murray Dale; Duncan Faulkner (International Journal of Climatology, 2021)
Recent flooding related to extreme precipitation in the UK has highlighted the importance of better understanding these events. Many studies have quantified annual exceedance probabilities (or return periods) for UK extreme daily precipitation using fixed regions (e.g., HadUKP) and region of interest (ROI) (e.g., Flood Estimation Handbook) approaches, although fewer have evaluated short‐duration events, which are important for flash flooding. Existing UK extreme precipitation regions are based on daily datasets which have different characteristics compared to sub‐daily extremes, and their application to quantify short‐duration extremes may therefore be inappropriate. We use a recently available, quality‐controlled hourly precipitation dataset for the UK from 1992 to 2014 to derive various extreme precipitation indices (e.g., annual maxima, 0.99 quantile) which are combined with additional climatological variables (e.g., temperature), geographical characteristics (e.g., latitude), and weather patterns (WPs) to characterize the UK hourly extreme precipitation climatology and to define five new hourly extreme regions. These regions fulfil regional homogeneity and discordancy statistical measures, and reflect the dynamical processes associated with the weather pattern categorisation defined over the UK and surrounding European area. Thereafter, we use regional frequency analysis (RFA) to fit generalized extreme value (GEV) and generalized Pareto (GP) distributions to 1 hr annual maxima (AMAX) and 0.99 quantile (Q99) precipitation, respectively, to calculate regional annual probability estimates (AEP) for 20%, 10%, and 2% (i.e., 5‐, 10‐, and 50‐year return periods). The new regions capture the spatial variation of hourly precipitation across the UK. Furthermore, the AEP estimates using both distributions are similar for each region. Finally, the WPs associated with the frequency and intensity of the most extreme hourly precipitation accumulations are not identical to results reported by others for daily precipitation.

Correction to: In Vitro to In Vivo Extrapolation of Metabolic Clearance for UGT Substrates Using Short-Term Suspension and Long-Term Co-cultured Human Hepatocytes - Luca Docci; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Kenichi Umehara; Isabelle Walter; Stephan Krähenbühl; Neil Parrott; Stephen Fowler (The AAPS Journal, 2020)

In Vitro to In Vivo Extrapolation of Metabolic Clearance for UGT Substrates Using Short-Term Suspension and Long-Term Co-cultured Human Hepatocytes - Luca Docci; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Kenichi Umehara; Isabelle Walter; Stephan Krähenbühl; Neil Parrott; Stephen Fowler (The AAPS Journal, 2020)

Construction and Verification of Physiologically Based Pharmacokinetic Models for Four Drugs Majorly Cleared by Glucuronidation: Lorazepam, Oxazepam, Naloxone, and Zidovudine - Luca Docci; Kenichi Umehara; Stephan Krähenbühl; Stephen Fowler; Neil Parrott (The AAPS Journal, 2020)

Atmospheric precursors for intense summer rainfall over the United Kingdom - Richard P. Allan; Stephen Blenkinsop; Hayley J. Fowler; Adrian J. Champion (International Journal of Climatology, 2020)
Intense sub‐daily summer rainfall is linked to flooding impacts in the United Kingdom. Characterizing the atmospheric conditions prior to the rainfall event can improve understanding of the large‐scale mechanisms involved. The most intense sub‐daily rainfall intensity data generated from rain gauge records across the United Kingdom over the period 1979–2014 are combined with fields from the ERA Interim reanalysis to characterize atmospheric conditions prior to heavy rainfall events. The 200 most intense 3‐hourly events for six UK regions are associated with negative anomalies in sea level pressure (

Global distribution of the intensity and frequency of hourly precipitation and their responses to ENSO - Xiao-Feng Li; Stephen Blenkinsop; Renaud Barbero; Jingjing Yu; Elizabeth Lewis; Geert Lenderink; Selma Guerreiro; Steven Chan; Yafei Li; Haider Ali; Roberto Villalobos Herrera; Elizabeth Kendon; et al. (Climate Dynamics, 2020)
We investigate the global distribution of hourly precipitation and its connections with the El Niño–Southern Oscillation (ENSO) using both satellite precipitation estimates and the global sub-daily rainfall gauge dataset. Despite limited moisture availability over continental surfaces, we find that the highest mean and extreme hourly precipitation intensity (HPI) values are mainly located over continents rather than over oceans, a feature that is not evident in daily or coarser resolution data. After decomposing the total precipitation into the product of the number of wet hours (NWH) and HPI, we find that ENSO modulates total precipitation mainly through the NWH, while its effects on HPI are more limited. The contrasting responses to ENSO in NWH and HPI is particularly apparent at the rising branches of the Pacific and Atlantic Walker Circulations, and is also notable over land-based gauges in Australia, Malaysia, the USA, Japan and Europe across the whole distribution of hourly precipitation (i.e. extreme, moderate and light precipitation). These results provide new insights into the global precipitation distribution and its response to ENSO forcing.

UKGrsHP: a UK high-resolution gauge–radar–satellite merged hourly precipitation analysis dataset - Jingjing Yu; Xiao-Feng Li; Elizabeth Lewis; Stephen Blenkinsop; Hayley J. Fowler (Climate Dynamics, 2020)
There is an urgent need for high-quality and high-spatial-resolution hourly precipitation products around the globe, including the UK. Although hourly precipitation products exist for the UK, these either contain large errors, or are insufficient in spatial resolution. An efficient way to solve this is to develop a merged precipitation product that combines the information and benefits from multiple data sources, improving both the spatial resolution and accuracy of hourly precipitation estimates over the UK. In this study, we develop a UK high-resolution gauge–radar–satellite merged hourly precipitation analysis: the UKGrsHP. It covers the UK from 12.5° W to 3.5° E, 49° N–60° N, with a spatial resolution of 0.01° × 0.01° in latitude/longitude (equivalent to 1 km resolution in the mid-latitudes). An optimal interpolation (OI)–based multi-source merging scheme with compound strategy is developed and tested for producing the UKGrsHP. Three input data sources are used: gauge analysis data interpolated from 1903 quality-controlled hourly observations, the UK Nimrod radar precipitation analysis and the GSMaP global satellite precipitation analysis. Using independent tests against ~ 220 independent gauge observations on 1 year’s experimental UKGrsHP, covering the period from January to December 2014, we find that the final merged data performs better than three individual precipitation analyses used as inputs. A full version of the UKGrsHP starting in April 2004 is now under production, which will have wide applications in climate services and scientific research across multiple disciplines.

Downscaling climate change of mean climatology and extremes of precipitation and temperature: Application to a Mediterranean climate basin - Rong Zhang; João Corte‐Real; Madalena Moreira; Chris Kilsby; Aidan Burton; Hayley J. Fowler; Stephen Blenkinsop; Stephen Birkinshaw; Nathan Forsythe; João P. Nunes; Elsa Sampaio (International Journal of Climatology, 2019)
Downscaling is usually necessary for robust hydrological impact assessments. This may be undertaken using a wide range of methods, including a combination of dynamical and statistical‐stochastic downscaling. This study uses the Spatial–Temporal Neyman‐Scott Rectangular Pulses model—RainSimV3, the precipitation‐conditioned daily weather generator—ICAAM‐WG, and the change factor approach for downscaling synthetic climate scenarios for robust hydrological impact assessment at middle‐sized basins. The ICAAM‐WG was developed based on the concept of the Climate Research Unit daily weather generator (CRU‐WG), motivated by the need for improved representation of heat waves by downscaling methods given the positive feedback between low soil moisture and high air temperature. We demonstrated the validity of the proposed methodology in the 705‐km 2 Mediterranean climate basin in southern Portugal. The results show that, for the control period 1980–2010, both RainSimV3 and ICAAM‐WG reproduced not only the mean climatology, but also extreme wet and low precipitation events, as well as the extremes of temperature and heat waves. We found that downscaling with ICAAM‐WG (SIM6), which uses second‐order autoregressive processes for the simulation of temperature during consecutive dry and wet days, outperformed ICAAM‐WG (SIM4), which used only first‐order autoregressive processes, leading to improved simulation of heat waves. ICAAM‐WG (SIM6) well reproduced observed heatwave extremes with return periods of up to 30 years; however, ICAAM‐WG (SIM4) overestimated these extremes substantially. This indicates the importance of incorporating second‐order autoregressive processes in the simulation of heatwave length. In the context of climate warming, the proposed methodology provides a tool to improve downscaled projections of future extremes with confidence intervals for not only wet events but also dry spells and heat waves.

Thermodynamic controls of the Western Tibetan Vortex on Tibetan air temperature - Xiao-Feng Li; Hayley J. Fowler; Jingjing Yu; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2019)

Impact of Intracellular Concentrations on Metabolic Drug-Drug Interaction Studies - Andrea Treyer; Mohammed Ullah; Neil Parrott; Birgit Molitor; Stephen Fowler; Per Artursson (The AAPS Journal, 2019)

Downscaling climate change of water availability, sediment yield and extreme events: Application to a Mediterranean climate basin - Rong Zhang; João Corte‐Real; Madalena Moreira; Chris Kilsby; Stephen Birkinshaw; Aidan Burton; Hayley J. Fowler; Nathan Forsythe; João Pedro Nunes; Elsa Sampaio; Francisco Lúcio dos Santos; Sandra Mourato (International Journal of Climatology, 2019)
A robust hydrological impact assessment is indispensable for mitigation and adaptation planning. This study presents an integrated modelling methodology for evaluating climate change impacts on water availability, sediment yield and extreme events at the catchment scale. We propose the use of the spatial–temporal Neyman–Scott Rectangular Pulses (STNSRP) model—RainSim V3 and the rainfall conditioned daily weather generator—ICAAM‐WG, as well as the physically based spatially distributed hydrological model—SHETRAN. The change factor approach was applied for obtaining unbiased rainfall and temperature statistics. The ICAAM‐WG was developed based on the modified Climate Research Unit daily Weather Generator (CRU‐WG). The methodology is proposed to generate synthetic series of hourly precipitation, daily temperature and potential evapotranspiration, hourly runoff and hourly sediment discharge. We demonstrated a possible application in a 705‐km 2 Mediterranean climate basin in southern Portugal. The case study showed the evaluation of future climate change impacts on annual and monthly water balance components and sediment yield, annual and seasonal flow duration curves, empirical extreme value distributions and the theoretical fits. It did not consider the possible uncertainty due to the limit of computational resources. The methodology can be well justified as follows: (a) the use of synthetic hourly instead of daily precipitation enables SHETRAN to be more capable of reproducing reliable storm runoff processes and the consequent sediment transport processes; (b) the use of SHETRAN makes possible the impact assessment to be accessible for any model grid square within the study basin; (c) the use of a statistical–stochastic downscaling method facilitates the generation of the synthetic series with unlimited length. It makes possible robust hydrological impact assessments if uncertainties related to the global climate model, regional climate model, greenhouse gas emission scenario, downscaling method, hydrological model and observational data are considered.

The Karakoram/Western Tibetan vortex: seasonal and year-to-year variability - Xiao-Feng Li; Hayley J. Fowler; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2018)

A regional frequency analysis of UK sub‐daily extreme precipitation and assessment of their seasonality - Motasem M. Darwish; Hayley J. Fowler; Stephen Blenkinsop; Mari R. Tye (International Journal of Climatology, 2018)
Floods related to extreme precipitation events, especially intense, short‐duration precipitation, may cause significant damage in urbanized areas, including transport infrastructure, electricity networks, and property. These events are expected to increase in frequency with climate change but their characteristics, at either hourly or multi‐hourly timescales, have been little studied due to short and poor quality data records. We examine annual maximum (AMAX) hourly and multi‐hourly (3, 6, 12, and 24 hr) precipitation accumulations in the United Kingdom using a quality‐controlled hourly precipitation data set for the period 1992–2014. We describe their seasonality and diurnal cycle and use a regional frequency analysis (RFA) approach with L ‐moments to produce at‐site return level estimates, and then use existing extreme precipitation regions to provide regional‐scale return levels. The analysis shows a clear seasonality and the dominant occurrence of short‐duration AMAX in summer with similar seasonality for 1 and 3 hr accumulation periods in some regions, while longer‐duration AMAX (12 and 24 hr) behave similarly to each other in all regions but are distributed over a longer period including late autumn and winter. The diurnal cycle of 1 hr AMAX indicates that most extremes occur during the afternoon, with a peak typically between 1400 and 1700, especially in southern and eastern regions. However, we also demonstrate that existing regions for UK daily extremes are not able to adequately reflect differences at shorter durations and that new regions should be created. These results provide new insights to help in designing urban drainage systems and infrastructure, including the need for new scaling relationships between sub‐daily and design accumulation periods.

Regional frequency analysis of extreme rainfall in Sicily (Italy) - Angelo Forestieri; Francesco Lo Conti; Stephen Blenkinsop; Marcella Cannarozzo; Hayley J. Fowler; Leonardo V. Noto (International Journal of Climatology, 2018)
Extreme rainfall events have large impacts on society and are likely to increase in intensity under climate change. For design and management decisions, particularly regarding hydraulic works, accurate estimates of precipitation magnitudes are needed at different durations. In this article, an objective approach of the regional frequency analysis (RFA) has been applied to precipitation data for the island of Sicily, Italy. Annual maximum series for rainfall with durations of 1, 3, 6, 12, and 24 h from about 130 rain gauges were used. The RFA has been implemented using principal component analysis (PCA) followed by a clustering analysis, through the k ‐means algorithm, to identify statistically homogeneous groups of stations for the derivation of regional growth curves. Three regional probability distributions were identified as appropriate from an initial wider selection of distributions and were compared – the three‐parameter log‐normal distribution (LN3), the generalized extreme value (GEV) distribution, and the two component extreme value (TCEV) distribution. The regional parameters of these distributions were estimated using L‐moments and considering a hierarchical approach. Finally, assessment of the accuracy of the growth curves was achieved by means of the relative bias and relative root‐mean‐square error (RMSE) using a simulation analysis of regional L‐moments. Results highlight that for the lower return periods, all distributions showed the same accuracy while for higher return periods the LN3 distribution provided the best result. The study provides an updated resource for the estimation of extreme precipitation quantiles for Sicily through the derivation of growth curves needed to obtain depth–duration–frequency (DDF) curves.

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Metabolic Profiling of Human Long-Term Liver Models and Hepatic Clearance Predictions from In Vitro Data Using Nonlinear Mixed-Effects Modeling - Nicole A. Kratochwil; Christophe Meille; Stephen Fowler; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Sandrine Simon; Isabelle Walter; Claudia McGinnis; Johanna Walther; Brian Leonard; Miriam Triyatni; et al. (The AAPS Journal, 2017)

Humanizing the zebrafish liver shifts drug metabolic profiles and improves pharmacokinetics of CYP3A4 substrates - Kar Lai Poon; Xingang Wang; Ashley S. Ng; Wei Huang Goh; Claudia McGinnis; Stephen Fowler; Tom J. Carney; Haishan Wang; Phillip W. Ingham (Archives of Toxicology, 2017)

Progress in Prediction and Interpretation of Clinically Relevant Metabolic Drug-Drug Interactions: a Minireview Illustrating Recent Developments and Current Opportunities - Stephen Fowler; Peter N. Morcos; Yumi Cleary; Meret Martin-Facklam; Neil Parrott; Michael Gertz; Li Yu (Current Pharmacology Reports, 2017)

Quality‐control of an hourly rainfall dataset and climatology of extremes for the UK - Stephen Blenkinsop; Elizabeth Lewis; Steven C. Chan; Hayley J. Fowler (International Journal of Climatology, 2017)
Sub‐daily rainfall extremes may be associated with flash flooding, particularly in urban areas but, compared with extremes on daily timescales, have been relatively little studied in many regions. This paper describes a new, hourly rainfall dataset for the UK based on ∼1600 rain gauges from three different data sources. This includes tipping bucket rain gauge data from the UK Environment Agency (EA), which has been collected for operational purposes, principally flood forecasting. Significant problems in the use of such data for the analysis of extreme events include the recording of accumulated totals, high frequency bucket tips, rain gauge recording errors and the non‐operation of gauges. Given the prospect of an intensification of short‐duration rainfall in a warming climate, the identification of such errors is essential if sub‐daily datasets are to be used to better understand extreme events. We therefore first describe a series of procedures developed to quality control this new dataset. We then analyse ∼380 gauges with near‐complete hourly records for 1992–2011 and map the seasonal climatology of intense rainfall based on UK hourly extremes using annual maxima, n ‐largest events and fixed threshold approaches. We find that the highest frequencies and intensities of hourly extreme rainfall occur during summer when the usual orographically defined pattern of extreme rainfall is replaced by a weaker, north–south pattern. A strong diurnal cycle in hourly extremes, peaking in late afternoon to early evening, is also identified in summer and, for some areas, in spring. This likely reflects the different mechanisms that generate sub‐daily rainfall, with convection dominating during summer. The resulting quality‐controlled hourly rainfall dataset will provide considerable value in several contexts, including the development of standard, globally applicable quality‐control procedures for sub‐daily data, the validation of the new generation of very high‐resolution climate models and improved understanding of the drivers of extreme rainfall.

Effects of Morphine on Behavioral Task Performance in SIV-Infected Rhesus Macaques - Joanne K. Marcario; Gurudutt Pendyala; Mariam Riazi; Kandace Fleming; Janet Marquis; Shannon Callen; Steven J. Lisco; Stephen C. Fowler; Paul D. Cheney; Shilpa J. Buch (Journal of Neuroimmune Pharmacology, 2016)

Genomic deletions and mutations resulting in the loss of eight genes reduce the in vivo replication capacity of Meleagrid herpesvirus 1 - Timothy J. Mahony; Robyn N. Hall; Stephen Walkden-Brown; Joanne Meers; Jennifer L. Gravel; Lani West; Vanessa Hardy; A.F.M. Fakhrul Islam; Elizabeth V. Fowler; Neena Mitter (Virus Genes, 2015)

Objective classification of extreme rainfall regions for the UK and updated estimates of trends in regional extreme rainfall - Mari R. Jones; Stephen Blenkinsop; Hayley J. Fowler; Christopher G. Kilsby (International Journal of Climatology, 2014)
Extreme rainfall events pose considerable threats to society and critical infrastructure yet, by definitions, these events are rare. Reliable estimates of the likelihood of such events are required to assist with impact quantification and risk management. Regional frequency analysis of pooled extreme rainfall to estimate the likely impacts of a changing climate is a well established method to assess the probability of these extremes. Previous analyses of country‐wide changes to UK extreme daily rainfall have used the 9 Hadley UK Precipitation ( HadUKP ) regions (Alexander and Jones, 2000), which are not appropriate for use with extremes. While these characterize well the mean daily intensity and frequency within each region, extreme rainfall climatology differs from that of the mean characteristics. As a result the existing HadUKP regions do not represent extreme rainfall behaviour adequately, with regard to the frequency, intensity or timing of extreme events. Focussing on many extreme rainfall characteristics, such as the seasonal timing and magnitude of maxima, this article presents a formal representation of extreme regions which specifically describe extreme spatial and temporal characteristics. The article concludes with a brief exploration of improved event estimation using these extreme rainfall regions. The new regional definitions provide clearer upward trends in annual maxima over the period 1961–2010 than those estimated using the HadUKP regional pools. © 2013 Royal Meteorological Society

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

An assessment of changes in seasonal and annual extreme rainfall in the UK between 1961 and 2009 - Mari R. Jones; Hayley J. Fowler; Christopher G. Kilsby; Stephen Blenkinsop (International Journal of Climatology, 2013)
There is a growing body of evidence supporting the Intergovernmental Panel on Climate Change's contestation that changes to hydrological extremes as a result of anthropogenic climate change are likely. There is also a growing level of concern among water resource managers about the nature of these changes and how we might adapt our behaviour to accommodate them. In particular, extreme multi‐day rainfall events have been a significant contributing factor to the severe flood events of recent years. Here we provide an updated study of extreme rainfall in the UK, focussing on changes to seasonal and annual maxima over the period 1961‐2009. We employ regional frequency analysis to examine changes in the magnitude of estimated return periods obtained from generalized extreme value distribution curves. Return period estimates are analysed using both the full record and using 10 year intervals to determine the relative importance of natural variability and long‐term changes in extreme rainfall distribution. The magnitude of changes in estimated return periods are spatially varied, and dominated in northern and western parts of the UK by a periodic forcing such as the North Atlantic Oscillation (NAO), superimposed on normal seasonal fluctuations. In contrast, seasonality has the greatest influence on event magnitude in the south and east. We confirm that previously reported increases in spring and autumn extreme rainfall events have continued. Similarly, longer duration winter events have continued to increase in intensity, with a decrease in return period estimate from a 25‐year to around a 5‐year event over the full 50 years of record in parts of Scotland and Southwest England. In contrast, short‐duration summer rainfall events have continued to decline in intensity, whereas longer duration events appear to be increasing in intensity. These results may have significant implications for flood defence design and planning, as well as to agricultural practices which may be sensitive to extreme rainfall. Copyright © 2012 Royal Meteorological Society

Mass Spectrometry-Based Quantification of CYP Enzymes to Establish In Vitro/In Vivo Scaling Factors for Intestinal and Hepatic Metabolism in Beagle Dog - Aki T. Heikkinen; Arno Friedlein; Jens Lamerz; Peter Jakob; Paul Cutler; Stephen Fowler; Tara Williamson; Roberto Tolando; Thierry Lave; Neil Parrott (Pharmaceutical Research, 2012)

A multi-model ensemble of downscaled spatial climate change scenarios for the Dommel catchment, Western Europe - Michelle T. H. van Vliet; Stephen Blenkinsop; Aidan Burton; Colin Harpham; Hans Peter Broers; Hayley J. Fowler (Climatic Change, 2012)

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

Timing and space usage are disrupted by amphetamine in rats maintained on DRL 24-s and DRL 72-s schedules of reinforcement - Stephen C. Fowler; Jonathan Pinkston; Elena Vorontsova (Psychopharmacology, 2009)

In Vitro Evaluation of Reversible and Irreversible Cytochrome P450 Inhibition: Current Status on Methodologies and their Utility for Predicting Drug–Drug Interactions - Stephen Fowler; Hongjian Zhang (The AAPS Journal, 2008)

Stereotyped and complex motor routines expressed during cocaine self-administration: results from a 24-h binge of unlimited cocaine access in rats - Stephen C. Fowler; Herbert E. Covington; Klaus A. Miczek (Psychopharmacology, 2007)

Clozapine and prazosin slow the rhythm of head movements during focused stereotypy induced by d-amphetamine in rats - Stephen C. Fowler; Jonathan W. Pinkston; Elena Vorontsova (Psychopharmacology, 2007)

Behavioral sensitization to amphetamine in rats: changes in the rhythm of head movements during focused stereotypies - Stephen C. Fowler; Brenda Birkestrand; Rong Chen; Elena Vorontsova; Troy Zarcone (Psychopharmacology, 2003)

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Concurrent quantification of tremor and depression of locomotor activity induced in rats by harmaline and physostigmine - Guanghui Wang; Stephen Fowler (Psychopharmacology, 2001)

Effects of haloperidol and clozapine on tongue dynamics during licking in CD-1, BALB/c and C57BL/6 mice - Guanghui Wang; Stephen C. Fowler (Psychopharmacology, 1999)

Microbehavioral methods for measuring the motor and associative effects of dopamine receptor antagonists and related drugs in rodents - Stephen C. Fowler (Psychopharmacology, 1999)

Dopamine-transporter occupancy after intravenous doses of cocaine and methylphenidate in mice and humans - S. J. Gatley; Nora D. Volkow; Andrew N. Gifford; Joanna S. Fowler; Stephen L. Dewey; Yu-Shin Ding; Jean Logan (Psychopharmacology, 1999)

Chronic haloperidol produces a time- and dose-related slowing of lick rhythm in rats: implications for rodent models of tardive dyskinesia and neuroleptic-induced parkinsonism - Stephen C. Fowler; Guanghui Wang (Psychopharmacology, 1998)

Subchronic effects of clozapine and haloperidol on rats' forelimb force and duration during a press-while-licking task - J. A. Stanford; Stephen C. Fowler (Psychopharmacology, 1997)